2017
DOI: 10.1177/1934578x1701200116
|View full text |Cite
|
Sign up to set email alerts
|

Constituents of Fermented Male Flowers of Alnus sieboldiana (Betulaceae)

Abstract: Fractionation of the ethyl acetate crude extract of the fermented male flowers of Alnus sieboldiana resulted in the isolation of two diarylheptanoids and six flavonoids. Yashabushidiol A, yashabushidiol B and naringenin were known constituents of the male flowers of A. sieboldiana while kaempferol, quercetin, pinocembrin dimethyl ether, 5,7-dimethoxy-3-hydroxyflavanone and 5,7-dimethoxy-3-hydroxyflavone were isolated for first time from the fermented male flowers of A. sieboldiana. The isolated compounds were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…According to the previous literature, peaks 3 and 4 were presumed to be 3’,7-dimethoxy-3-hydroxyflavone isomers. 32 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the previous literature, peaks 3 and 4 were presumed to be 3’,7-dimethoxy-3-hydroxyflavone isomers. 32 …”
Section: Resultsmentioning
confidence: 99%
“…Fragment ions at m/z 284, m/z267, m/z239, m/z211, m/z181 and m/z153 were probably produced by a series of neutral losses from the parent ion corresponding to [M+H-CH 3 ] + , [M+H-CH 3 -OH] + , [M+H-CH 3 -OH-CO] + , [M+H-CH 3 -OH-(CO) 2 ] + , [M+H-CH 3 -OH-(CO) 2 -CH 2 O] + and [M+H-CH 3 -OH-(CO) 3 -CH 2 O] + ,respectively. According to the previous literature, peaks 3 and 4 were presumed to be 3',7-dimethoxy-3-hydroxyflavone isomers 32. As for peak 5, the[M+H] + ion at m/z 465 was obtained.…”
mentioning
confidence: 87%
“…The contents of naringenin and pinocembrin were reduced after a 6-month fermentation while new compounds such as kaempferol, quercetin, pinocembrin dimethyl ether, 5,7-dimethoxy-3-hydroxyflavanone, and 5,7-dimethoxy-3-hydroxyflavone were produced through bioconversion. Authors suggested that the hydroxylation of naringenin at positions C-3 and C-3 produced kaempferol and quercetin, respectively, while methylation, hydroxylation, and oxidation of pinocembrin gave three 5,7-dimethoxyflavonoids [42]. Pei et al [43] reported production of kaempferol and astragalin through fermentation.…”
Section: Fermentation Of Plant-based Materials As Source Of Biopestic...mentioning
confidence: 99%